Effects of Prone Positioning for Patients with Acute Respiratory Distress Syndrome Caused by Pulmonary Contusion: A Single-Center Retrospective Study - Xiaoyi Liu; Hui Liu; Shilian Liu; Wenlai Zhou; Qing Lan; Jun Duan; Xue Li; Xiangde Zheng (Canadian Respiratory Journal)
Background. The effects of prone positioning (PP) on patients with acute respiratory distress syndrome (ARDS) caused by pulmonary contusion (PC) are unclear. We sought to determine the efficacy of PP among patients whose ARDS was caused by PC. Methods. A retrospective observational study was performed at an intensive care unit (ICU) from January 2017 to June 2021. ARDS patients with PaO2/FiO2 (P/F) < 150 mmHg were enrolled. During the study period, we enrolled 121 patients in the PP group and 117 in the control group. The changes in vital signs, laboratory tests, and compliance of the respiratory system (Crs) were recorded for 3 consecutive days. The mechanical ventilation time, duration of ICU stay, complications, extubation rate, 28-day ventilator-free days, and mortality were also recorded. Results. In the PP group, the P/F and Crs increased over time. Compared to the control group, the P/F and Crs improved in the PP group over 3 consecutive days (P<0.05). Furthermore, the PP group also had shorter total mechanical ventilation time (5.1 ± 1.4 vs. 9.3 ± 3.1 days, P<0.05) and invasive ventilation time (4.9 ± 1.2 vs. 8.7 ± 2.7 days, P<0.05), shorter ICU stay (7.4 ± 1.8 vs. 11.5 ± 3.6days, P<0.05), higher extubation rate (95.6% vs. 84.4%, P<0.05), less atelectasis (15 vs. 74, P<0.05) and pneumothorax (17 vs. 24, P>0.05), more 28-day ventilator-free days (21.6 ± 5.2 vs. 16.2 ± 7.2 days, P<0.05), and lower mortality (4.4% vs. 13.3%, P<0.05). Conclusions. Among PC cases with moderate to severe ARDS, PP can correct hypoxemia more quickly, improve Crs, reduce atelectasis, increase the extubation rate, shorten mechanical ventilation time and length of ICU stay, and reduce mortality.